Karya Ilmiah Remaja sebagai Upaya Pengembangan Minat dan Bakat di SMA Syubbanul Wathon Tegalrejo: Youth Scientific Work as an Effort to Develop Interests and Talents at Syubbanul Wathon Tegalrejo Senior High School - Az Zafi, Ashif; Putri, Dwi Wahyu; Nisa’Auliya, Siti Qurrotu A’yun; Husna, Karina Fikriatil; Maudita, Widiya (TA'LIMUNA: Jurnal Pendidikan Islam, 2024)
Youth Scientific Work (Karya Ilmiah Remaja; KIR) is an intra-school organization as an extracurricular at the junior high school, senior high school, madrasah and even Islamic boarding school (pesantren) level as a forum for developing student creativity and potential through scientific writing activities which have the main objective of advancing the development of student interests and talents. Through Youth Scientific Work, students have the opportunity to explore various topics that suit their interests, thus providing a richer and more satisfying learning experience. Therefore, the extracurricular Youth Scientific Work program can encourage students to think creatively and develop innovative ideas. This paper aims to find out the efforts to develop students' interests and talents at Syubbanul Wathon Tegalrejo Senior High School through the Youth Scientific Work extracurricular program. The research methodology used in this study is a qualitative approach with a focus on observation and interviews.  The findings of this study indicate that the Youth Scientific Work extracurricular program provides benefits and positive impacts on the development of students' interests and talents at Syubbanul Wathon Tegalrejo Senior High School. Through Youth Scientific Work, students' skills in both research and writing can be improved. Karya Ilmiah Remaja (KIR) merupakan organisasi intra sekolah sebagai ekstrakurikuler di tingkat SMP, SMA, Madrasah bahkan pondok pesantren, sebagai wadah pengembangan kreativitas dan potensi siswa melalui kegiatan penulisan karya ilmiah yang memiliki tujuan utama untuk memajukan pengembangan minat dan bakat siswa. Melalui KIR, siswa memiliki kesempatan untuk mengeksplorasi berbagai topik yang sesuai dengan minat mereka, sehingga memberikan pengalaman belajar yang lebih kaya dan memuaskan. Oleh karena itu, program ekstrakurikuler KIR dapat mendorong siswa untuk berpikir kreatif dan mengembangkan ide-ide inovatif. Artikel ini ditujukan untuk mengetahui upaya pengembangan minat dan bakat siswa di SMA Syubbanul Wathon Tegalrejo melalui program ekstrakurikuler KIR. Metodologi penelitian yang digunakan adalah pendekatan kualitatif dengan fokus pada observasi dan wawancara. Temuan penelitian ini menunjukkan bahwa program ekstrakurikuler KIR memberi manfaat dan dampak positif bagi perkembangan minat dan bakat siswa di SMA Syubbanul Wathon Tegalrejo. KIR juga dapat meningkatkan keterampilan siswa pada bidang penelitian maupun penulisan. Keywords: Karya Ilmiah Remaja (KIR), Minat, Bakat, SMA Syubbanul Wathon